Answer:
(a)3-2=1 (b) 4-3=1 (c) 12-1-1=10
To solve this function, all we need to do is substitute -4.3 in for wherever "x" appears and then simplify.
f(x) = 7.45x + 33.7; x = -4.3
f(-4.3) = 7.45(-4.3) + 33.7
f(-4.3) = -32.035 + 33.7
f(-4.3) = 1.665
This means that, when x = -4.3, f(x) = 1.665.
Note: It may help to remember that, in a function such as this, f(x) can be thought of as the "y" value that corresponds to the given "x" value (in fact, when writing it out with words, f(x) is the same as "function of x"). And, if you are given a value for f(x), then the opposite is true. Just substitute in the value given for f(x) and solve for x.
Hope this helps!
6/x=27
times both sides by x
6=27x
divide both sides by 27
6/27=x
2/9=x
the missing number is 2/9
Answer: (x, y) = (-x, -y)
Step-by-step explanation:
To solve this, you can match the coordinates of points on the triangles and choose the correct answer from there.
The highest point on the triangle, S, has coordinates of (3, 5).
The reflected triangle's point S has coordinates of (-3, -5).
Point Q on the triangle has coordinates of (1, 0)
Point Q on the reflected triangle has coordinates of (-1, 0).
Matching these two points and their reflections to the answers, the only answer that fulfills both points correctly is (x, y) = (-x, -y).
Answer:
H=21ft
Step-by-step explanation:
Height=2•Area/Base
Area=126ft^2
Base=12ft.
H=2•126/12=21ft
H=21ft
Hope this helps :)